APLIKASI SISTEM INFORMASI PARIWISATA TOURISM PADA DKI JAKARTA BERBASIS ANDROID - Mohamad Natsir (Sekolah Tinggi Teknik - PLN, 2019)
DKI Jakarta has many characteristics both in terms of attractions, culture, crafts and culinary. Jakarta is an attractive capital city and is often visited by tourists from various regions and abroad. So from that writing makes an application about tourist information in the City of Jakarta based on Android. Users of this application are expected to easily find tourist information in the city of Jakarta. Information contained in the application in the form of tourist attractions. The application also displays the direction of the location to that place using the Global Possitioning System (GPS) connection. The method used in this application is to contain information and location of each place in the city of Jakarta such as tourist attractions. Each menu selected has information and directions to reach the desired place. This application is only used on Android-based smartphones and the screen size is less than 4.0 inches, besides the size of 4.0 inches this application is not good at displaying tourist information.